INTERLEAVED 4-PHASES DC/DC CONVERTER FOR ELECTRIC SCOOTER TO IMPROVE EFFICIENCY - SIHAB, AIDA SYAFIQAH (2017)
This project presents the design of an Interleaved DC/DC Boost Converter for the implementation of an Electric Scooter. The output of the power converter can be controlled using the Pulse Width Modulation (PWM) switching technique to boost 12V battery supply to power a 24V Brushed DC Motor with improved efficiency compared to conventional converters. The design of the power converter was finalized with the parameters optimization using calculation. The simulation is carried out using MATLAB/Simulink Software. The PWM output switching frequency is set to 25 kHz with 4 signals of 90° phase shift to each other. The current measured at the input of the inductor for Interleaved 4-phases Converter is 0.6826A compared to 0.5245A for a conventional converter with the increment of 30.14%. Besides, the voltage output ripple is significantly reduced with the implementation of interleaving technique from 0.2% to only 0.04% while current output ripple is reduced from 36.38% to 16.31%. The details of the design based on previous researches are included together with the theoretical analysis to validate the result.